Associations between blood glucose level and outcomes of adult in-hospital cardiac arrest: a retrospective cohort study. Issue 1 (December 2016) - Wang, Chih-Hung; Huang, Chien-Hua; Chang, Wei-Tien; Tsai, Min-Shan; Yu, Ping-Hsun; Wu, Yen-Wen; Chen, Wen-Jone
Abstract Background We intended to analyse the associations between blood glucose (BG) level and clinical outcomes of in-hospital cardiac arrest (IHCA). Methods We conducted a retrospective observational study in a single medical centre and evaluated patients who experienced IHCA between 2006 and 2014. We used multivariable logistic regression analysis to study associations between independent variables and outcomes. We calculated the mean BG level for each patient by averaging the maximum and minimum BG levels in the first 24 h after arrest, and we used mean BG level for our final analysis. Results We included a total of 402 patients. Of these, 157 patients (39.1 %) had diabetes mellitus (DM). The average mean BG level was 209.9 mg/dL (11.7 mmol/L). For DM patients, a mean BG level between 183 and 307 mg/dL (10.2–17.1 mmol/L) was significantly associated with favourable neurological outcome (odds ratio [OR] 2.71, 95 % confidence interval [CI] 1.18–6.20;p value = 0.02); a mean BG level between 147 and 317 mg/dL (8.2–17.6 mmol/L) was significantly associated with survival to hospital discharge (OR 2.38, 95 % CI 1.26–4.53; p value = 0.008). For non-DM patients, a mean BG level between 143 and 268 mg/dL (7.9–14.9 mmol/L) was significantly associated with survival to hospital discharge (OR 2.93, 95 % CI 1.62–5.40; p value < 0.001). Conclusions Mean BG level in the first 24 h after cardiac arrest was associated with neurological outcome for IHCA patients with DM. For neurological and survival outcomes, the optimal BG range may be higher for patients with DM than for patients without DM.